Use a transformation to solve the equation.



z – (–0.3) = –2.4

Question 2 options:

z = –2.7

z = 2.7

z = –2.1

z = 2.1

1 answer

To solve the equation using a transformation, we can add 0.3 to both sides of the equation:

z - (-0.3) + 0.3 = -2.4 + 0.3

This simplifies to:

z = -2.1

Therefore, the solution is z = -2.1.
Similar Questions
  1. Use a transformation to solve the equation.h + (–3) = –0.6 Question 3 options: h = –2.4 h = 2.4 h = –3.6 h = 3.6
    1. answers icon 1 answer
  2. Use a transformation to solve the equation.n + 11.5 = –29 Question 5 options: n = –17.5 n = 40.5 n = 17.5 n = –40.5
    1. answers icon 1 answer
  3. Use a transformation to solve the equation.Mathml image Question 4 options: w = –32 w = –2 w = 2 w = 32
    1. answers icon 1 answer
  4. Use a transformation to solve the equation.Mathml image Question 4 options: w = –32 w = –2 w = 2 w = 32
    1. answers icon 1 answer
more similar questions